Not Completely a Company Town - Rosenfeld, Herman (Socialist Project: The Bullet, 2020)
Peter Findlay’s documentary film Company Town provides a welcome opening to initiate discussion and debate about the closure of General Motor’s once massive (it had 23,000 workers at one time) and historically central auto and truck complex and supplier plants. Behind the film’s basic narrative is a countdown from the period between the announcement (November 2018) of the closure and the actual end of production (December 2019). It creates space to raise issues such as the power and strategic orientation of the union and its leadership, the nature of the industry and competition in this era of late neoliberal capitalism, the consciousness and lives of auto and parts workers, and the possibilities of alternatives. –Introduction